The Christology of St Anthony of Padua: content and method. Issue 1 (2nd January 2019) - Severn, Paul
ABSTRACT: In 1946 St Anthony of Padua (1195–1231) was declared a Doctor of the Church, recognised for his profound learning. Whereas much has been written about St Anthony, very little of it concerns his profound learning – and so it is not inappropriate to ask wherein this learning lies. Reading St Anthony reveals Christological concerns to be at the heart of his work and in this paper the author explores and clarifies his position. However, anyone looking for new and exciting Christological insights is likely to be disappointed, for St Anthony is entirely orthodox and traditional, although we should not only consider the content of his work, but his 'method' too. The way that the saint presents doctrine, and the inferences he draws from it, has much to be commended. Indeed, St Anthony may well be contrasted with those modern theologians who, it has been suggested, have rather lost track of what it is they are really doing.